Geochemical fractions and modeling adsorption of heavy metals into contaminated river sediments in Japan and Thailand determined by sequential leaching technique using ICP-MS - Anugrah Ricky Wijaya; Shigeru Ohde; Ryuichi Shinjo; Monthon Ganmanee; Michael Dustin Cohen (My University, 2016)
In order to provide information on the chemical processes in sediment fractions and their adsorption models, we investigated the contaminated sediments of the Sumida River in Tokyo, Japan and the Chao Phraya River in Bangkok, Thailand. Samples were leached through a sequential leaching technique to perform metal concentration analysis for the sediment fraction assessment and then samples were tested for the model adsorption of the highest level of sediments contaminated by heavy metals using the isotherm Langmuir and Freundlich equations. Metal (Pb, Cd, Zn, As, Cu, Ca, Fe, and Mn) concentration in the leached solutions was analyzed by Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The pattern of geochemical fractions in both sediment samples showed the maxima leached levels of Cd (38.6 %), Ca (55.2%), and Mn (41.3%) in the soluble fraction; Pb (52.1%), and Zn (56.7%) in the reducible fraction; Cu (61.2%) in the oxidizable fraction; and As (47.1%) and Fe (55.9%) in the residual fraction. The total level fractions of Pb (62.6 ppm), Zn (240 ppm), As (27.2 ppm), Fe (16,636 ppm) and Mn (419 ppm) in the Chao Phraya River sediments were higher compared to those in the Sumida River, indicating the high anthropogenic effect in Bangkok. In the most contaminated sediments, the higher adsorption capacity of heavy metal concentrations was contributed by SiO2, CaCO3, and Al2O3 determined by the X-ray diffraction and organic contents. The model of adsorption of Cd fitted to the linear form of Langmuir's equation with the correlation coefficients (r2 = 0.94), b (0.467) and k (7137), whereas Pb, Cu, Cr, and Zn conformed to the model of the Freundlich equation.
Keywords: Langmuir adsorption model; Fraction (chemistry); Heavy metals in environment